2002
DOI: 10.1002/1099-0682(200205)2002:5<1162::aid-ejic1162>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Lanthanide(III) Ions with Polyhydroxy Carboxylic Acids in Aqueous Solutions

Abstract: The complexation of lanthanum(III), europium(III), dysprosium(III), erbium(III), and lutetium(III) with D‐gluconic acid (LH) was studied by pH potentiometry and NMR. The set of complexes formed in aqueous solutions and their stability constants β were determined, and the results were compared to those previously found for praseodymium(III) (S. Giroux et al., Polyhedron 2000, 19, 1567). A regular evolution of the β values was observed along the lanthanide series, particularly for the neutral complex MLH−2 (wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 25 publications
4
49
0
Order By: Relevance
“…The thermodynamic observation for the participation of the hydroxyl group into the complexation is also in agreement with Giroux et al's work [7], where 13 C NMR data confirmed the involvement of ␣-hydroxyl group of gluconate in the coordination to Pr(III). Table 3 summarizes the measured thermodynamic parameters of gluconate protonation [11] and its complexation with Ca 2+ and NpO 2 + [11] at 25 • C and 1.0 M NaClO 4 .…”
Section: Log β − Pk a Correlation For Nd(iii)/monocarboxylate Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic observation for the participation of the hydroxyl group into the complexation is also in agreement with Giroux et al's work [7], where 13 C NMR data confirmed the involvement of ␣-hydroxyl group of gluconate in the coordination to Pr(III). Table 3 summarizes the measured thermodynamic parameters of gluconate protonation [11] and its complexation with Ca 2+ and NpO 2 + [11] at 25 • C and 1.0 M NaClO 4 .…”
Section: Log β − Pk a Correlation For Nd(iii)/monocarboxylate Complexmentioning
confidence: 99%
“…Several studies on the complexation of gluconic acid with lanthanides [1][2][3][4][5][6][7][8] and actinides [9,10] can be found in the literature. Stability constants were reported in these studies, but no other thermodynamic properties (e.g., enthalpies) were provided.…”
Section: Introductionmentioning
confidence: 99%
“…The solution of 1 in D 2 O was adjusted to pH 1 with DCl (20% w/w in D 2 O, 99.5 at.% D, from CIL) to ensure near complete protonation of the carboxyl group. In organic solvents, 1 (pK a in H 2 O D 3.52) 39 was assumed to exist essentially as the undissociated acid. The anion 2 was prepared by addition of tetrabutylammonium cyanide and dissolution in methanol under a nitrogen atmosphere, followed by concentration to dryness.…”
Section: Sample Preparation and Nmr Spectramentioning
confidence: 99%
“…[105]. The proton displacement from the OH group of gluconate also holds for other lanthanides, such as La 3+ , Pr 3+ and Eu 3+ [31,126]. Along with the 1:1:-1 and 1:1:-2 species, complexes with the stoichiometry of 1:2:-1, 1:2:-2 and 1:2:-3 were also reported [121][122][123][124].…”
Section: Complex Formation Between Nd 3+ and D-gluconate Ionsmentioning
confidence: 99%
“…It is noteworthy that the dependence of the complexation on the metal ion concentration was not investigated in spite of its importance in detecting multinuclear complexes. Such species were found to be formed with copper(II) [28,30,108], calcium(II) [62] and europium(III) [126].…”
Section: Complex Formation Between Nd 3+ and D-gluconate Ionsmentioning
confidence: 99%